Study on the Interface Effects Based on Two-Dimensional Green's Functions for the Fluid and Pyroelectric Two-Phase Plane under a Line Heat Source - Peng-Fei Hou; Wei Tian; Ke Yuan (Advances in Mechanical Engineering, 2014)
Two-dimensional Green's functions for a line heat source applied in the fluid and pyroelectric two-phase plane are presented in this paper. By virtue of the two-dimensional general solutions which are expressed in harmonic functions, six newly introduced harmonic functions with undetermined constants are constructed. Then, all the pyroelectric components in the fluid and pyroelectric two-phase plane can be derived by substituting these harmonic functions into the corresponding general solutions. And the undetermined constants can be obtained by the interface compatibility conditions and the mechanical, electric, and thermal equilibrium conditions. Numerical results are given graphically by contours.